Using DNA metabarcoding to assess dietary selection and seasonal dietary patterns in eastern hellbenders (Cryptobranchus alleganiensis) - Daniel D. Knapp; Shem Unger; Jelsie Kerr; Lori A. Williams; Allison L. DeLoache; Catherine M. Bodinof Jachowski (Food Webs, 2026)

Multimorbidity as a predictor of mortality in companion dogs - Eric R. Foreman; Laura Corlin; Kate E. Creevy; Jessica M. Hoffman; Joshua M. Akey; Rozalyn M. Anderson; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Matthew D. Dunbar; Virginia R. Fajt; Erica C Jonlin; et al. (GeroScience, 2026)

The effects of aerobic and resistance exercise on the lipid profile of extracellular vesicles - Tesha Kerr Carpenter; Mariah McCashland; Raechel Sherrick; Sathish Kumar Natarajan; Mirko Mandić; Stephen D. Kachman; Ferdinand von Walden; Ivan J. Vechetti; Rodrigo Fernandez-Gonzalo (European Journal of Applied Physiology, 2026)
Purpose Lipids are one of the most abundant molecules within extracellular vesicles (EVs) and are important for EV biology and cell signaling. However, very little attention has been given to the role of lipids in the biological function of EVs during exercise. Therefore, we completed a study using a cross-over design to investigate the effects of aerobic and resistance exercise on the lipid profile of EVs. Methods Ten healthy participants (23.0 ± 3.6 years) performed an acute bout of aerobic exercise, an acute bout of resistance exercise, as well as a period of rest (control) in a randomized, cross-over design. Blood samples were collected immediately following exercise and 30 min after exercise, and exercise conditions were compared to control within each subject. Plasma EVs were isolated using cushioned-density gradient ultracentrifugation (C-DGUC). The EV size, morphology, and protein markers were examined using nanoflow cytometry, transmission electron microscopy, and western blot, respectively. Additionally, we conducted an untargeted lipidomics analysis on the EV isolate. Results Our findings revealed neither exercise modality had a significant effect on the size or concentration of EVs ( P > 0.05). However, we found that immediately after exercise there was a decrease in glycerophospholipids within the EVs (55% vs 49%; P < 0.05) in the resistance exercise group compared to the control group, a response not found in the aerobic exercise group. Conclusion Our data suggest that although resistance exercise induced some changes in the lipid composition of EVs, the EV-containing lipids do not appear to be a critical mechanism utilized by cells to mediate exercise-induced adaptations. Graphical Abstract

Development of burn prescriptions using quantitative expert judgement - Jane G. Cawson; Jamie E. Burton; Kate A. Parkins; Erica Marshall; Shona Elliot-Kerr; Nicola Aylward; Mel Calwell; Hamish Martin; Trent D. Penman (Journal of Environmental Management, 2025)

Skeletal muscle atrophy induced by aging and disuse atrophy are strongly associated with the upregulation of the endoplasmic stress protein CHOP in rats - J. Max Michel; Joshua S. Godwin; Nathan R. Kerr; Thomas E. Childs; Frank W. Booth; C. Brooks Mobley; David C. Hughes; Michael D. Roberts (Molecular Biology Reports, 2025)
Background While canonical anabolic and proteolytic pathways have been well examined in the context of skeletal muscle proteostasis, the roles of endoplasmic reticulum stress (ERS) and the induced unfolded protein response (UPR) are underappreciated. Thus, we aimed to determine whether aging and/or disuse atrophy in rats altered skeletal muscle ERS/UPR markers. Methods and Results Soleus (SOL) and plantaris (PLT) muscles of 3-month-old (mo), 6 mo, 12 mo, 18 mo, and 24 mo rats (9–10 per group, 48 in total) were analyzed for UPR proteins with further analysis performed on the protein CHOP. The gastrocnemius muscles of 4 mo rats that had undergone hindlimb immobilization (HLI, n = 12) or sham casting (CTL, n = 12) were analyzed for similar targets as well as more extensive CHOP-related targets. CHOP protein was greater in the PLT and SOL of 18 and 24 mo rats versus other age groups ( P < 0.05). Moreover, negative correlations existed between CHOP expression and normalized PLT ( R =-0.702, P < 0.001) and SOL ( R =-0.658, P < 0.001) muscle weights in all rats analyzed at different ages. CHOP protein expression was also greater in the gastrocnemius of HLI versus CTL rats ( P < 0.001), and a negative correlation existed between CHOP protein expression and normalized muscle weights in these rats ( R =-0.814, P < 0.001). Nuclear CHOP protein levels ( P < 0.010) and genes transcriptionally regulated by CHOP were also greater in HLI versus CTL rats ( P < 0.001) implicating transcriptional activity of CHOP is elevated during disuse atrophy. Conclusions CHOP is operative during aging- and disuse-induced skeletal muscle atrophy in rodents, and more research is needed to determine if CHOP is a key mechanistic driver of these processes.

Optimisation of bronchoalveolar lavage fluid preparation for mononuclear cell isolation and cytologic evaluation in free-ranging African elephants (Loxodonta africana) - Stacey C. Engel; Tanya J. Kerr; Gian D. van der Spuy; Tracey Jooste; Peter E. Buss; Jennifer L. Johns; Michele A. Miller; Léanie Kleynhans (Veterinary Immunology and Immunopathology, 2025)

Spatial and Temporal Heterogeneity of Fish Spawning Dynamics on the West Florida Shelf During Fall - Keith Keel; Makenzie Kerr; Laura Y. Liu; Yonggang Liu; Joshua P. Kilborn; Glenn Zapfe; Ernst B. Peebles; Christopher D. Stallings; Mya Breitbart (Fisheries Oceanography, 2025)
Identifying spawning areas for economically and ecologically important fishes is critical for fisheries conservation and ecosystem‐based management. We used genetic barcoding to identify fish eggs collected across the West Florida Shelf (WFS) during September of 2013, 2014, and 2019. Fish eggs were collected on Southeast Area Monitoring and Assessment Program (SEAMAP) ichthyoplankton cruises using a Continuous Underway Fish Egg Sampler. Analysis of 4833 fish eggs from the 3 years resulted in the identification of 82 species within 35 families. A 78% DNA barcoding success rate was achieved, with 46% of all identifications being at the species level. PERMANOVA results revealed significant differences in fish egg beta‐diversity across time (the 3 years sampled) and space (preassigned levels of both depth class and regional strata). Our findings generally aligned with known adult fish distributions and spawning patterns, and we found that water‐column depth played a more important role than regional strata in structuring the fish egg assemblages. Eggs from several economically important species were collected and observed at relatively high frequencies, including red snapper, lane snapper, vermilion snapper, yellowedge grouper, and king mackerel. We used the West Florida Coastal Ocean Model to hindcast the trajectories of all fish eggs and trace them back to possible spawning locations. We conducted backward tracking over a span of 36 h based on the assumption that most fish eggs on the WFS undergo hatching within this time window. The model estimated egg transport distances ranging from 1 to 79 km (mean distance of ~21 km), with greater transport distances estimated on the outer shelf in comparison to the middle and inner shelf. These results further our understanding of the spatial and interannual variation of fish spawning dynamics on the WFS and mark the beginning of a long‐term monitoring effort.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

5-HT2C agonism as a neurotherapeutic for sarcopenia: preclinical proof of concept - Nathan R. Kerr; Anna R. Dashtmian; Fereshteh B. Darvishi; Charles D. Brennan; Sindhuja N. Ayyagari; Peter J. Moore; Jose A. Viteri; Meifang Wang; Mark M. Rich; Brian C. Clark; W. David Arnold (GeroScience, 2025)

Advancements in Riverine Fish Movement Modeling: Bridging Environmental Complexity and Fish Behavior - D. P. Zielinski; J. Kerr; K. M. Bærum; O. M. Simmons; A. T. Silva; R. A. Goodwin (Reviews in Fisheries Science & Aquaculture, 2025)

Assessing the effect of multispecies interactions on precautionary reference points using an ensemble modelling approach: A North Sea case study - Michael A. Spence; James A. Martindale; Khatija Alliji; Hayley J. Bannister; Robert B. Thorpe; Nicola D. Walker; Peter J. Mitchell; Matthew R. Kerr; Paul J. Dolder (Fisheries Research, 2024)

Expert assessment of illegal collecting impacts on Venus flytraps and priorities for research on illegal trade - Jared D. Margulies; Benjamin Trost; Laura Hamon; Natalie Z. Kerr; Michael Kunz; John L. Randall; Roger D. Shew; Dale M. Shew; Lesley Starke; Dale Suiter; Zachary West (Conservation Biology, 2024)
Illegal collecting of wild Venus flytraps ( Dionaea muscipula ) for the horticultural trade represents a persistent threat to populations of the species across their endemic range in the coastal plain of North and South Carolina (United States). Although wild collecting of Venus flytraps is not a novel threat, there has been very little research on the impacts of collecting on the species’ conservation to date or why an illegal trade persists alongside a legal one. We drew on qualitative expert stakeholder elicitation to contextualize the threat of illegal collecting to the long‐term conservation of Venus flytraps in relation to other anthropogenic threats. Expert elicitation included botanical and conservation researchers, cognizant state and federal agency staff, land managers, and conservation nonprofit actors. The workshop included mapping of supply chain structures and prioritization of social and environmental harms. Expert consensus determined illegal collecting is an ongoing problem for Venus flytrap conservation, but habitat destruction, degradation, and fire suppression are the most significant threats to flytrap conservation. Supply chain analysis showed that observable social and environmental harms of the trade are focused at the supply stage and that less is known about transit and demand stages. Key research gaps identified include a lack of understanding of plant laundering practices relevant to a range of desirable plant taxa; the role of commercial nurseries in illicit horticultural supply chains; motivations for engaging in Venus flytrap collecting; and the persistent demand for illegally harvested plants when cultivated, legally obtainable plants are readily available. Our findings and methodology are relevant to a range of ornamental plants affected by illegal trade for which robust social data on illegal collecting drivers are lacking.

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Defining the Sheldon Creek Formation, a Middle Wisconsinan (MIS 3) till in Iowa, USA - STEPHANIE A. Tassier‐Surine; PHILLIP J. Kerr; SUSAN M. Kilgore; BRADLEY D. Cramer (Journal of Quaternary Science, 2024)
A pre‐Late Wisconsinan, post‐Illinoian, till sheet has long been recognized in north‐central Iowa, but has not been formally recognized or defined until now. Early researchers referred to these deposits as the ‘Tazewell’, and the term ‘Sheldon Creek’ was more recently used informally by the Iowa Geological Survey in guidebooks and reports. Recent mapping has extended the eastern margin significantly past previous interpretations. The Sheldon Creek Formation has similar lithologic characteristics to the overlying Alden Member of the Dows Formation, and the two units are distinguished mainly by stratigraphic position. Differentiation from underlying Pre‐Illinoian till units is accomplished using lithology, primarily matrix grain‐size and sand fraction lithology. A suite of 22 radiocarbon ages indicate two distinct, separate groupings within the Sheldon Creek data. These data strongly suggest ice advanced south to 42° N twice, once during Marine Isotope Stage (MIS) 3 and again during late MIS 3 or possibly early MIS 2. The presence of the Laurentide Ice Sheet in northern Iowa during MIS 3 has significant implications for ice sheet reconstructions during this interval.

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

Retention and export of planktonic fish eggs in the northeastern Gulf of Mexico - Bich Vi Viviane Nguyen; Yonggang Liu; Christopher D. Stallings; Mya Breitbart; Steven A. Murawski; Robert H. Weisberg; Makenzie Kerr; Eva‐Maria S. Bønnelycke; Ernst B. Peebles (Fisheries Oceanography, 2024)
To help determine whether planktonic eggs of fishes on the West Florida Shelf (WFS) are retained locally or exported elsewhere, we collected fish eggs by plankton net from 17 locations (stations) and identified them using DNA barcoding. We then entered the station coordinates into the West Florida Coastal Ocean Model (WFCOM) and simulated the trajectories of the passively drifting eggs over 2 weeks at three depths (surface, midwater, and near bottom). The results indicated there were two groups of trajectories: a nearshore group that tended to be retained and an offshore group that tended toward export and potential long‐distance dispersal. We also found evidence of a relationship between retention and higher fish‐egg abundance; nearshore stations were associated with higher fish‐egg abundances and higher retention. We suggest this is the result of (1) increased spawning in high‐retention areas, (2) increased drift convergence in high‐retention areas, or both processes acting together. Community analysis using SIMPROF indicated the presence of a depth‐related (retention‐related) difference in species assemblages. Fish‐egg species were also categorized as pelagics or non‐pelagics; there was no evidence of pelagic species being more likely to be exported.

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Correction to: Inflammasome‑Regulated Pyroptotic Cell Death in Disruption of the Gut‑Brain Axis After Stroke - Nadine A. Kerr; Juliana Sanchez; Gregory O’Connor; Brant D. Watson; Sylvia Daunert; Helen M. Bramlett; W. Dalton Dietrich (Translational Stroke Research, 2023)

Costs of preventing and supressing wildfires in Victoria, Australia - Erica Marshall; Shona Elliot-Kerr; Sarah C. McColl-Gausden; Trent D. Penman (Journal of Environmental Management, 2023)

Soil Moisture and Sea Surface Salinity Derived from Satellite-Borne Sensors - J. Boutin; S. Yueh; R. Bindlish; S. Chan; D. Entekhabi; Y. Kerr; N. Kolodziejczyk; T. Lee; N. Reul; M. Zribi (Surveys in Geophysics, 2023)
The monitoring of soil moisture and sea surface salinity over the Earth has been profoundly enhanced during the last thirteen years due to a new generation of satellite sensors. L-band radiometry is currently the only technology providing direct measurements of soil moisture, insensitive to surface roughness and distribution of elements in the soil, and the only technology the only technology for measuring that allows us to measure sea surface salinity from space. The Soil Moisture and Ocean Salinity (SMOS) and Soil Moisture Active Passive (SMAP) satellite missions resolve global and local variability with a spatial resolution of approximately 43 km, a swath width close to 1000 km, and a sampling time, for each mission, of at least twice every 3 days. These resolutions and samplings can be increased by either merging data from the two sensors, and with complementary information gathered from other passive or active sensors, or with in situ information at higher spatial resolution. Numerous scientific studies based on the use of this new type of measurement have led to a better understanding and constraint of the processes governing the variability of the water cycle, ocean circulation and the Earth's climate. The continuity of measurements, and the increased spatial and radiometric resolution is critical for fulfilling scientific needs. Future L-band radiometry missions currently being planned in Europe (the Copernicus Imaging Microwave Radiometer), and in China (the Ocean Salinity mission) should provide better constraints on auxiliary parameters by combining multiple frequencies, but they will not have improved spatial resolution beyond SMOS and SMAP. The temporal continuity with SMOS and SMAP will likely not be ensured. In parallel, new concepts are being developed to increase spatial resolution of both land and ocean parameters.

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Enhanced skeletal muscle contractile function and corticospinal excitability precede strength and architectural adaptations during lower-limb resistance training - Matthew T. Wilson; Angus M. Hunter; Malcolm Fairweather; Stewart Kerr; D. Lee Hamilton; Lewis J. Macgregor (European Journal of Applied Physiology, 2023)
Purpose Evolving investigative techniques are providing greater understanding about the early neuromuscular responses to resistance training among novice exercisers. The aim of this study was to investigate the time-course of changes in muscle contractile mechanics, architecture, neuromuscular, and strength adaptation during the first 6-weeks of lower-limb resistance training. Methods Forty participants: 22 intervention (10 males/12 females; 173.48 ± 5.20 cm; 74.01 ± 13.13 kg) completed 6-week resistance training, and 18 control (10 males/8 females; 175.52 ± 7.64 cm; 70.92 ± 12.73 kg) performed no resistance training and maintained their habitual activity. Radial muscle displacement (Dm) assessed via tensiomyography, knee extension maximal voluntary contraction (MVC), voluntary activation (VA), corticospinal excitability and inhibition via transcranial magnetic stimulation, motor unit (MU) firing rate, and muscle thickness and pennation angle via ultrasonography were assessed before and after 2, 4, and 6-weeks of dynamic lower-limb resistance training or control. Results After 2-weeks training, Dm reduced by 19–25% in the intervention group; this was before any changes in neural or morphological measures. After 4-weeks training, MVC increased by 15% along with corticospinal excitability by 16%; however, there was no change in VA, corticospinal inhibition, or MU firing rate. After 6-weeks training there was further MVC increase by 6% along with muscle thickness by 13–16% and pennation angle by 13–14%. Conclusion Enhanced contractile properties and corticospinal excitability occurred before any muscle architecture, neural, and strength adaptation. Later increases in muscular strength can be accounted for by architectural adaptation.

The need to include wild foods in climate change adaptation strategies - Bronwen Powell; Indra D. Bhatt; Megan Mucioki; Suresh Rana; Sandeep Rawat; Rachel Bezner Kerr (Current Opinion in Environmental Sustainability, 2023)

Consequences of ignoring climate impacts on New England groundfish stock assessment and management - Mackenzie D. Mazur; Jerelle Jesse; Steven X. Cadrin; Samuel B. Truesdell; Lisa Kerr (Fisheries Research, 2023)

Greenness modifies the association between ambient air pollution and cognitive function in Australian adolescents, but not in mid-life adults - Yichao Wang; Mallery Crowe; Luke D. Knibbs; Matthew Fuller-Tyszkiewicz; Lærke Mygind; Jessica A. Kerr; Melissa Wake; Craig A. Olsson; Peter G. Enticott; Rachel L. Peters; Galina Daraganova; Suzanne Mavoa; et al. (Environmental Pollution, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

CRISPR-knockout of β-kafirin in sorghum does not recapitulate the grain quality of natural mutants - Karen Massel; Jessica Hintzsche; Jemma Restall; Edward D. Kerr; Benjamin L. Schulz; Ian D. Godwin (Planta, 2023)

Inflammasome-Regulated Pyroptotic Cell Death in Disruption of the Gut-Brain Axis After Stroke - Nadine A. Kerr; Juliana Sanchez; Gregory O’Connor; Brant D. Watson; Sylvia Daunert; Helen M. Bramlett; W. Dalton Dietrich (Translational Stroke Research, 2022)

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Antimony Mobilisation and Attenuation During Ore Processing at Orogenic Gold Mines, Southern New Zealand - E. Weightman; D. Craw; T. Snow; G. Kerr (Mine Water and the Environment, 2022)

Long‐term, low incidence of web‐decorating by spiders in the Mariana Islands, Micronesia - Alexander M. Kerr; Joanne D. Sablan; Michelle K. Williams; Ferdinand Galsim; Philip C. Guerrero; Abram L. Townsend; J. Kawika Davis; Gregorio C. Borja; Ryszard Z. Oleksy; John F. Furey; David L. Benavente; Erin M. Derrington; et al. (Ecology, 2021)

Agile management and long-term strategy in exploration: the ‘lucky’ discovery of the Sinclair Pollucite Deposit, Eastern Goldfields, Western Australia - G. E. Batt; D. Crook; N. Brand; S. Kerr (Australian Journal of Earth Sciences, 2021)

Brain activation and connectivity in anorexia nervosa and body dysmorphic disorder when viewing bodies: relationships to clinical symptoms and perception of appearance - Teena D. Moody; Francesca Morfini; Gigi Cheng; Courtney L. Sheen; Wesley T Kerr; Michael Strober; Jamie D. Feusner (Brain Imaging and Behavior, 2021)

Light-Weight Portable Electroantennography Device as a Future Field-Based Tool for Applied Chemical Ecology - Stephen M. Pawson; Jessica L. Kerr; Brooke C. O’Connor; Philippe Lucas; Dominique Martinez; Jeremy D. Allison; Tara M. Strand (Journal of Chemical Ecology, 2020)

Symbiont community diversity is more variable in corals that respond poorly to stress - Lauren I. Howe‐Kerr; Benedicte Bachelot; Rachel M. Wright; Carly D. Kenkel; Line K. Bay; Adrienne M. S. Correa (Global Change Biology, 2020)
Coral reefs are declining globally as climate change and local water quality press environmental conditions beyond the physiological tolerances of holobionts—the collective of the host and its microbial symbionts. To assess the relationship between symbiont composition and holobiont stress tolerance, community diversity metrics were quantified for dinoflagellate endosymbionts (Family: Symbiodiniaceae) from eight Acropora millepora genets that thrived under or responded poorly to various stressors. These eight selected genets represent the upper and lower tails of the response distribution of 40 coral genets that were exposed to four stress treatments (and control conditions) in a 10‐day experiment. Specifically, four ‘best performer’ coral genets were analyzed at the end of the experiment because they survived high temperature, high p CO 2 , bacterial exposure, or combined stressors, whereas four ‘worst performer’ genets were characterized because they experienced substantial mortality under these stressors. At the end of the experiment, seven of eight coral genets mainly hosted Cladocopium symbionts, whereas the eighth genet was dominated by both Cladocopium and Durusdinium symbionts. Symbiodiniaceae alpha and beta diversity were higher in worst performing genets than in best performing genets. Symbiont communities in worst performers also differed more after stress exposure relative to their controls (based on normalized proportional differences in beta diversity), than did best performers. A generalized joint attribute model estimated the influence of host genet and treatment on Symbiodiniaceae community composition and identified strong associations among particular symbionts and host genet performance, as well as weaker associations with treatment. Although dominant symbiont physiology and function contribute to host performance, these findings emphasize the importance of symbiont community diversity and stochasticity as components of host performance. Our findings also suggest that symbiont community diversity metrics may function as indicators of resilience and have potential applications in diverse disciplines from climate change adaptation to agriculture and medicine.

Widespread drought‐induced tree mortality at dry range edges indicates that climate stress exceeds species' compensating mechanisms - William R. L. Anderegg; Leander D. L. Anderegg; Kelly L. Kerr; Anna T. Trugman (Global Change Biology, 2019)
Drought‐induced tree mortality is projected to increase due to climate change, which will have manifold ecological and societal impacts including the potential to weaken or reverse the terrestrial carbon sink. Predictions of tree mortality remain limited, in large part because within‐species variations in ecophysiology due to plasticity or adaptation and ecosystem adjustments could buffer mortality in dry locations. Here, we conduct a meta‐analysis of 50 studies spanning >100 woody plant species globally to quantify how populations within species vary in vulnerability to drought mortality and whether functional traits or climate mediate mortality patterns. We find that mortality predominantly occurs in drier populations and this pattern is more pronounced in species with xylem that can tolerate highly negative water potentials, typically considered to be an adaptive trait for dry regions, and species that experience higher variability in water stress. Our results indicate that climate stress has exceeded physiological and ecosystem‐level tolerance or compensating mechanisms by triggering extensive mortality at dry range edges and provides a foundation for future mortality projections in empirical distribution and mechanistic vegetation models.

Staying cool: the importance of shade availability for tropical ectotherms - C.-C. Chou; D. M. Perez; S. Johns; R. Gardner; K. A. Kerr; M. L. Head; E. L. McCullough; P. R. Y. Backwell (Behavioral Ecology and Sociobiology, 2019)

Effects of Δ9-THC and cannabidiol vapor inhalation in male and female rats - Mehrak Javadi-Paydar; Jacques D. Nguyen; Tony M. Kerr; Yanabel Grant; Sophia A. Vandewater; Maury Cole; Michael A. Taffe (Psychopharmacology, 2018)

Influence of subject presentation on interpretation of body composition change after 6 months of self-selected training and diet in athletic males - Ava D. Kerr; Gary J. Slater; Nuala M. Byrne (European Journal of Applied Physiology, 2018)

Effects of auditory and visual stimuli on shark feeding behaviour: the disco effect - Laura A. Ryan; Lucille Chapuis; Jan M. Hemmi; Shaun P. Collin; Robert D. McCauley; Kara E. Yopak; Enrico Gennari; Charlie Huveneers; Ryan M. Kempster; Caroline C. Kerr; Carl Schmidt; Channing A. Egeberg; et al. (Marine Biology, 2018)

Assessment of in silico protein sequence analysis in the clinical classification of variants in cancer risk genes - Iain D. Kerr; Hannah C. Cox; Kelsey Moyes; Brent Evans; Brianna C. Burdett; Aric van Kan; Heather McElroy; Paris J. Vail; Krystal L. Brown; Dechie B. Sumampong; Nicholas J. Monteferrante; Kennedy L. Hardman; et al. (Journal of Community Genetics, 2017)

K-complexes, spindles, and ERPs as impulse responses: unification via neural field theory - M. S. Zobaer; R. M. Anderson; C. C. Kerr; P. A. Robinson; K. K. H. Wong; A. L. D’Rozario (Biological Cybernetics, 2017)

Negative niche construction favors the evolution of cooperation - Brian D. Connelly; Katherine J. Dickinson; Sarah P. Hammarlund; Benjamin Kerr (Evolutionary Ecology, 2016)

Experimental Metalloid Mobilisation from a New Zealand Orogenic Gold Deposit - G. Kerr; J. Pope; D. Trumm; D. Craw (Mine Water and the Environment, 2015)

Jarosite Solid Solution Associated with Arsenic-Rich Mine Waters, Macraes Mine, New Zealand - G. Kerr; J. Druzbicka; K. Lilly; D. Craw (Mine Water and the Environment, 2015)

Divergence in DNA photorepair efficiency among genotypes from contrasting UV radiation environments in nature - Brooks E. Miner; Paige M. Kulling; Karlyn D. Beer; Benjamin Kerr (Molecular Ecology, 2015)
Populations of organisms routinely face abiotic selection pressures, and a central goal of evolutionary biology is to understand the mechanistic underpinnings of adaptive phenotypes. Ultraviolet radiation ( UVR ) is one of earth's most pervasive environmental stressors, potentially damaging DNA in any organism exposed to solar radiation. We explored mechanisms underlying differential survival following UVR exposure in genotypes of the water flea Daphnia melanica derived from natural ponds of differing UVR intensity. The UVR tolerance of a D. melanica genotype from a high‐ UVR habitat depended on the presence of visible and UV ‐A light wavelengths necessary for photoenzymatic repair of DNA damage, a repair pathway widely shared across the tree of life. We then measured the acquisition and repair of cyclobutane pyrimidine dimers, the primary form of UVR ‐caused DNA damage, in D. melanica DNA following experimental UVR exposure. We demonstrate that genotypes from high‐ UVR habitats repair DNA damage faster than genotypes from low‐ UVR habitats in the presence of visible and UV ‐A radiation necessary for photoenzymatic repair, but not in dark treatments. Because differences in repair rate only occurred in the presence of visible and UV ‐A radiation, we conclude that differing rates of DNA repair, and therefore differential UVR tolerance, are a consequence of variation in photoenzymatic repair efficiency. We then rule out a simple gene expression hypothesis for the molecular basis of differing repair efficiency, as expression of the CPD photolyase gene photorepair did not differ among D. melanica lineages, in both the presence and absence of UVR .

Comparison of locus-specific databases for BRCA1 and BRCA2 variants reveals disparity in variant classification within and among databases - Paris J. Vail; Brian Morris; Aric van Kan; Brianna C. Burdett; Kelsey Moyes; Aaron Theisen; Iain D. Kerr; Richard J. Wenstrup; Julie M. Eggington (Journal of Community Genetics, 2015)

Conference report: muskellunge science and management: progress through partnerships - Jonathan D. Midwood; Steven J. Kerr; Peter Levick; Steven J. Cooke (Environmental Biology of Fishes, 2015)

Characterisation of the genomes of four putative vesiculoviruses: tench rhabdovirus, grass carp rhabdovirus, perch rhabdovirus and eel rhabdovirus European X - David M. Stone; Rose C. Kerr; Margaret Hughes; Alan D. Radford; Alistair C. Darby (Archives of Virology, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Dosing of adult pigeons with as little as one #9 lead pellet caused severe δ-ALAD depression, suggesting potential adverse effects in wild populations - Jeremy P. Holladay; Mandy Nisanian; Susan Williams; R. Cary Tuckfield; Richard Kerr; Timothy Jarrett; Lawrence Tannenbaum; Steven D. Holladay; Ajay Sharma; Robert M. Gogal (Ecotoxicology, 2012)

Persistent Increase of Blood Lead Level and Suppression of δ-ALAD Activity in Northern Bobwhite Quail Orally Dosed With Even a Single 2-mm Spent Lead Shot - S. D. Holladay; R. Kerr; J. P. Holladay; B. Meldrum; S. M. Williams; R. M. Gogal (Archives of Environmental Contamination and Toxicology, 2012)

Genetic variation in PARL influences mitochondrial content - Joanne E. Curran; Jeremy B. M. Jowett; Lawrence J. Abraham; Luke A. Diepeveen; Katherine S. Elliott; Thomas D. Dyer; Lyndal J. Kerr-Bayles; Matthew P. Johnson; Anthony G. Comuzzie; Eric K. Moses; Ken R. Walder; Gregory R. Collier; et al. (Human Genetics, 2010)

Reconciling topographic and climatic effects on widespread and range‐restricted species richness - Nora D. Szabo; Adam C. Algar; Jeremy T. Kerr (Global Ecology and Biogeography, 2009)
Aim To identify the reasons behind differing geographical species richness patterns of range‐restricted and widespread species. Location The Western Hemisphere. Methods We used regression to determine the strongest environmental predictors of richness for widespread and range‐restricted mammal species in 10,000 km 2 quadrats in the continental Americas. We then used range‐placement models to predict the expected correlation between range‐restricted and widespread species richness were they to be determined by identical, random, or contrasting environmental factors. Finally, to determine the reasons underlying deviations from these predictions, we divided the Americas into 5% quantiles based on temperature and topographic heterogeneity and correlated richness of these two assemblages across quantiles – an approach that avoids constraints on statistical testing imposed by low potential for range overlap among range‐restricted species. Results Minimum annual temperature was the strongest predictor of widespread species richness while topographic heterogeneity was the best, although weak, predictor of range‐restricted species richness in conventional regression analysis. Our models revealed that the observed correlation between range‐restricted and widespread species richness was similar to what would be observed if both range‐restricted and widespread species richness were determined by temperature. Patterns of range‐restricted and widespread species richness were highly correlated across temperature quantiles, but range‐restricted species uniquely showed an increasing pattern across heterogeneity quantiles. Main conclusions Species richness gradients among range‐restricted species differ from those of widespread species, but not as extensively or for the reasons reported previously. Instead, these assemblages appear to share some but not all underlying environmental determinants of species richness. Our new approach to examining species richness patterns reveals that range‐restricted and widespread species richnesses share a common response to temperature that conventional analyses have not previously revealed. However, topographic heterogeneity has assemblage‐specific effects on range‐restricted species.

Effect of a 20-day ski trek on fuel selection during prolonged exercise at low workload with ingestion of 13C-glucose - F. Péronnet; M. Abdelaoui; C. Lavoie; C. Marrao; S. Kerr; D. Massicotte; G. Giesbrecht (European Journal of Applied Physiology, 2009)

The visual perceptual range of a lizard, Tiliqua rugosa - Zonnetje M. Auburn; C. Michael Bull; Gregory D. Kerr (Journal of Ethology, 2009)

An EST database for Liriodendron tulipifera L. floral buds: the first EST resource for functional and comparative genomics in Liriodendron - Haiying Liang; John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Lukas A. Mueller; Matyas Buzgo; Lena L. Landherr; Yi Hu; D. Scott DiLoreto; Daniel C. Ilut; Dawn Field; Steven D. Tanksley; et al. (Tree Genetics & Genomes, 2008)

Diagnosing Mitochondrial DNA Diversity: Applications of a Sentinel Gene Approach - Elizabeth L. Clare; Kevin C. R. Kerr; Taika E. von Königslöw; John J. Wilson; Paul D. N. Hebert (Journal of Molecular Evolution, 2008)

Differential expression of the keratan sulphate proteoglycan, keratocan, during chick corneal embryogenesis - E. Claire Gealy; Briedgeen C. Kerr; Robert D. Young; Debbie Tudor; Anthony J. Hayes; Clare E. Hughes; Bruce Caterson; Andrew J. Quantock; James R. Ralphs (Histochemistry and Cell Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Phylogeny and classification of Rosaceae - D. Potter; T. Eriksson; R. C. Evans; S. Oh; J. E. E. Smedmark; D. R. Morgan; M. Kerr; K. R. Robertson; M. Arsenault; T. A. Dickinson; C. S. Campbell (Plant Systematics and Evolution, 2007)

Differential immunogold localisation of sulphated and unsulphated keratan sulphate proteoglycans in normal and macular dystrophy cornea using sulphation motif-specific antibodies - Robert D. Young; Tomoya O. Akama; Petra Liskova; Neil D. Ebenezer; Bruce Allan; Briedgeen Kerr; Bruce Caterson; Michiko N. Fukuda; Andrew J. Quantock (Histochemistry and Cell Biology, 2006)

EST database for early flower development in California poppy (Eschscholzia californica Cham., Papaveraceae) tags over 6000 genes from a basal eudicot - John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Laura M. Zahn; Lukas A. Mueller; Lena L. Landherr; Yi Hu; Daniel C. Ilut; Jennifer M. Arrington; Stephanie Choirean; Annette Becker; Dawn Field; et al. (Plant Molecular Biology, 2006)

Differential regulation of caspase-3 by pharmacological and developmental stimuli as demonstrated using humanised caspase-3 mice - L. E. Kerr; J-L. A. Birse-Archbold; A. Simon; N. Logan; F. Scott; G. Carlson; D. W. Nicholson; J. S. Kelly; J. Sharkey (Apoptosis, 2004)

Definition of the domain boundaries is critical to the expression of the nucleotide-binding domains of P-glycoprotein - Ian D. Kerr; Georgina Berridge; Kenneth J. Linton; Christopher F. Higgins; Richard Callaghan (European Biophysics Journal, 2003)

Michigan residents’ perceptions of wetlands and mitigation - Michael D. Kaplowitz; John Kerr (Wetlands, 2003)

Characterisation of axon terminals in the rat dorsal horn that are immunoreactive for serotonin 5-HT3A receptor subunits - D. J. Maxwell; R. Kerr; S. Rashid; E. Anderson (Experimental Brain Research, 2003)

Laboratory Detection and Investigation of Reduced Susceptibility to Vancomycin in Oxacillin-Resistant Staphylococcus aureus - P. D. Midolo; T. M. Korman; D. Kotsanas; P. Russo; T. G. Kerr (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Myelinated and unmyelinated primary afferent axons form contacts with cholinergic interneurons in the spinal dorsal horn - M. J. Olave; N. Puri; R. Kerr; D. J. Maxwell (Experimental Brain Research, 2002)

Mutation analysis of the MECP2 gene in British and Italian Rett syndrome females - Marcella Vacca; Francesco Filippini; Alberta Budillon; Valeria Rossi; Grazia Mercadante; Elisa Manzati; Francesca Gualandi; Stefania Bigoni; Cecilia Trabanelli; Giorgio Pini; Elisa Calzolari; Alessandra Ferlini; et al. (Journal of Molecular Medicine, 2001)

Simulation studies on bacteriorhodopsin bundle of transmembrane α segments - Hyeon S. Son; Ian D. Kerr; Mark S.P. Sansom (European Biophysics Journal, 2000)

In Vitro Synergy Between Ranitidine Bismuth Citrate and Tetracycline or Clarithromycin Against Resistant Strains of Helicobacter pylori - P. D. Midolo; J. R. Lambert; T. G. Kerr; W. Tee (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Semiquantitative Polymerase Chain Reaction Enzyme Immunoassay for the Diagnosis of Pertussis - R. C. Matthews; N. Golbang; W. M. Brück; D. Owen; A. Bailey; V. Weston; J. R. Kerr (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Slant Column Measurements of O3 and NO2 During the NDSC Intercomparison of Zenith-Sky UV-Visible Spectrometers in June 1996 - H. K. Roscoe; P. V. Johnston; M. Van Roozendael; A. Richter; A. Sarkissian; J. Roscoe; K. E. Preston; J-C. Lambert; C. Hermans; W. DeCuyper; S. Dzienus; T. Winterrath; et al. (Journal of Atmospheric Chemistry, 1999)

Evidence of recovery from acidification in Massachusetts streams - Mark D. Mattson; Paul J. Godfrey; Marie-Françoise Walk; Peter A. Kerr; O. Thomas Zajicek (Water, Air, & Soil Pollution, 1997)

EVIDENCE OF RECOVERY FROM ACIDIFICATION IN MASSACHUSETTS STREAMS - MARK D. MATTSON; PAUL J. GODFREY; MARIE-FRANÇOISE WALK; PETER A. KERR; O. THOMAS ZAJICEK (Water, Air, & Soil Pollution, 1997)

Effects in s.e. Queensland during 1967–72 of insects introduced to controlLantana camara - K. L. S. Harley; J. D. Kerr; R. C. Kassulke (BioControl, 1979)